MOTIF PERNIKAHAN DINI MASYARAKAT SELOK ANYAR PASIRIAN LUMAJANG - Ayun, Qurroti; Hasyim, Rizky Putri Awaliyah (Dakwah, 2018)
Selok Anyar village is one of the villages located in Lumajang, whose traditional customs has been maintained until today especially in hinterland. Underage marriage is a common thing in society and even becomes a pride in the family. The formulation of the problem in this study is how the motives of Underage marriage in the community of Selok Anyar, Pasirian, Lumajang. This research is a descriptive qualitative research. Data collection is done through observation activities in  the field, interviews with informants in depth, and documentation. The results of the research display sociogenetic motives (surrounding environment, family encouragement), biogenetic motives (no compulsion from parents and other people), and theogenetic motives (avoid adultery and the willingness to migrate to be better). Key Words: Underage Marriage, Sociogenetic Motives, Traditional Customs